Development Strategy of PPM Al-Kautsar Micro Waqf Bank in Lima Puluh Kota Regency - Nurhafiani Nurhafiani; Azhari Akmal Tarigan; Muhammad Yafiz (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2022)
This research aims to find out and analyze the development strategy of the PPM Al-Kautsar Micro Waqf Bank in the Lima Puluh Kota Regency. The data analysis technique used is the SWOT analysis method (Strenght, Weakness, Opportunity, Threats). Based on the results of the SWOT matrix analysis, it is known that the strategy that can be carried out in developing a Micro Waqf Bank is stratetgi SO by using all strengths to take advantage of existing opportunities. The strategy is consistency of low mentoring services (ju'alah, without collateral and interest by utilizing government restructuring programs, utilizing the role of kyai in establishing good cooperation and building trust with institutions, local governments, the community socializing the existence of BWM, carrying out Halmi routines during a pandemic virtually and directly by complying with health protocols in providing education, direction, education to customers,  improving the quality of services and products even though it already exists with a ball pick-up system, optimizing the empowerment of mentoring through digital so that customers can survive during the pandemic despite social restrictions but empowerment continues to run. The strategy of developing BWM is to use BWM digitalization in providing virtual education, promoting customer products through e-commerce and social media, utilizing the role of kiyai in socializing BWM programs to the community Penelitain ini bertujuan untuk mengetahui strategi pengembangan Bank Wakaf Mikro PPM Al-Kautsar di Kabupaten Lima Puluh Kota?. Teknik analisis data yang digunakan adalah metode analisis SWOT (Strenght, Weakness,Opportunity, Threats). berdasarkan hasil analisis matriks SWOT diketahui bahwa strategi yang dapat dilakukan dalam  mengembangkan Bank Wakaf Mikro yaitu Stratetgi SO dengan menggunakan seluruh kekuatan unuk memanfaatkan peluang yang ada. Strateginya adalah Konsistensi jasa pendampingan rendah (jualah, tanpa agunan dan bunga dengan memanfaatkan program restrukturisasi pemerintah, memanfaatkan peran kiyai dalam menjalin kerja sama yang baik dan membangun kepercayaan dengan lembaga, pemerintah setempat, masyarakat mensosialisasikan keberadaan BWM, melakukan rutinitas Halmi saat pandemic secara virtual dan langsung dengan mematuhi protokol kesehatan dalam memberikan edukasi, arahan, pendidikan kepada nasabah, meningkatkan kualitas pelayanan dan produk meski sudah ada dengan sistem jemput bola, optimalisasi pemberdayaan pendampingan melalui digital supaya nasabah tetap bertahan saat pandemi meskipun adanya pembatasan sosial tetapi pemberdayaan tetap berjalan. Strategi mengembangkan BWM yaitu menggunakan digitalisasi BWM dalam memberikan edukasi secara virtual, mempromosikan produk-produk nasabah melalui e-commerce dan media sosial, memanfaatkan peran kiyai dalam mensosialisasikan program BWM kepada masyarakat.